Multilateralism Under Pressure: International Organizations and Great Power Rivalry in a Fragmented World - Mohamad Ichsana Nur (Pen of Global Politics, 2026)
Multilateralism remains a central feature of international order, yet international organizations now operate in an environment increasingly shaped by strategic rivalry and political fragmentation. As competition among major powers intensifies, shared institutions face growing pressure over authority, legitimacy, procedural fairness, and institutional direction. The purpose of this article is to examine how great power rivalry reshapes the role and political meaning of international organizations in a fragmented world. The article employs a qualitative research design based on document analysis and is guided by an order-based analytical framework that links multilateralism, institutional contestation, and fragmented governance. Data are drawn from international organization reports, official resolutions, summit declarations, policy documents, diplomatic records, and scholarly sources relevant to global governance and great power competition. The analysis focuses on institutional authority, strategic engagement, procedural inclusion, rivalry within multilateral settings, and the consequences of fragmentation for global order. International organizations remain active and politically relevant, but their authority is increasingly conditional, contested, and shaped by selective engagement from major powers. Multilateralism persists as an important mode of governance, yet it operates under altered political conditions in which cooperation and rivalry coexist within the same institutional arenas. The article contributes to the field by integrating debates on international organizations with a broader understanding of fragmented order and strategic contestation in world politics.